Food system digitalization and power shifts - Sodano, Valeria (Frontiers in Sustainable Food Systems, 2024)
The article provides new insights into the assessment of food system digitalization by analyzing how the entire process is mainly power-driven rather than the outcome of fair competition among alternative technological patterns. It focuses on the power forces that have accelerated the digital revolution in the food system and how this revolution is enabling certain subjects to exercise old and new forms of power in the economic, political, and geopolitical spheres. The analysis begins with a brief review of food digital technologies and how the existing literature has discussed their possible benefits and risks. It then focuses on the role of agenda power in promoting digitalization and on hegemonic power as the most important form of power produced by digitalization. The aim of the study is to offer a new perspective, based on the analysis of shifts from one form of political power to another, to better analyze the political issues raised by food system digitalization. The results suggest that to resist the negative aspects of digitalization, it is necessary to transform covert conflicts into overt ones and to understand the mechanisms through which the exercise of power blocks the transition from awareness of conflicts to political action.